Rinkos informacijos poreikių tyrimo problemos - Atkočiūnienė, Zenona (Information & Media, 1996)
The market has determined the creation of informational structures satisfying the market’s principles. Improving and creating new information systems investigation of informational demand is inevitable. Applying a method of prognosis, and a methodology of investigation of informational demand are presented in the article. It also grounds choice of number of expert groups and experts, presumptions of creation of automatized expert systems while increasing the value of presented information. The article reveals the principles of filling out the questionnaire using the logic of questions and answers.